DEVELOPMENT OF INTEGRATED SCIENCE LEARNING INSTRUMENTS USING A HUMANISTIC APPROACH WITH ECONOMIC DRAWINGS - Anis Zahrotin (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2021)
Research on the development of integrated science learning instruments helps students to develop their potential and character. The research involved the use of lesson plans, worksheets, syllabus, props and modules through four stages, namely the Four-D Model flow, namely definition, design, development, and dissemination. This research was conducted at MTsN 4 Bojonegoro. The research method is qualitative research by observing the field and collecting data based on the results of tests and questionnaires. The results of the study are as follows 1) students are more motivated to use teaching aids in integrated science learning, 2) by using economic teaching aids, students get an increase in cognitive knowledge and also character education and understand the relationship between knowledge and attitudes or actions in everyday life, 3) integrated science learning with economic aids should be used more intensively in science learning with different themes, 4) Each subject should provide opportunities for the teaching staff to develop economic teaching aids by utilizing used tools and materials from the surrounding environment.